Final results from a Phase 3, long‐term, open‐label, repeat‐dose safety study of diazepam nasal spray for seizure clusters in patients with epilepsy. (21st August 2021) - Wheless, James W.; Miller, Ian; Hogan, R. Edward; Dlugos, Dennis; Biton, Victor; Cascino, Gregory D.; Sperling, Michael R.; Liow, Kore; Vazquez, Blanca; Segal, Eric B.; Tarquinio, Daniel; Mauney, Weldon; et al.
Abstract: Objective: A Phase 3 open‐label safety study (NCT02721069) evaluated long‐term safety of diazepam nasal spray (Valtoco) in patients with epilepsy and frequent seizure clusters. Methods: Patients were 6–65 years old with diagnosed epilepsy and seizure clusters despite stable antiseizure medications. The treatment period was 12 months, with study visits at Day 30 and every 60 days thereafter, after which patients could elect to continue. Doses were based on age and weight. Seizure and treatment information was recorded in diaries. Treatment‐emergent adverse events (TEAEs), nasal irritation, and olfactory changes were recorded. Results: Of 163 patients in the safety population, 117 (71.8%) completed the study. Duration of exposure was ≥12 months for 81.6% of patients. There was one death (sudden unexpected death in epilepsy) and one withdrawal owing to a TEAE (major depression), both considered unlikely to be related to treatment. Diazepam nasal spray was administered 4390 times for 3853 seizure clusters, with 485 clusters treated with a second dose within 24 h; 53.4% of patients had monthly average usage of one to two doses, 41.7% two to five doses, and 4.9% more than five doses. No serious TEAEs were considered to be treatment related. TEAEs possibly or probably related to treatment ( n  = 30) were most commonly nasal discomfort (6.1%); headache (2.5%); and dysgeusia, epistaxis, and somnolence (1.8% each). Only 13 patients (7.9%) showed nasal irritation, and there were no relevant olfactory changes. The safety profile of diazepam nasal spray was generally similar across subgroups based on age, monthly usage, concomitant benzodiazepine therapy, or seasonal allergy/rhinitis. Significance: In this large open‐label safety study, the safety profile of diazepam nasal spray was consistent with the established profile of rectal diazepam, and the high retention rate supports effectiveness in this population. A second dose was used in only 12.6% of seizure clusters.